Cancer and Fertility - Sabanegh, Jr., Edmund S. (Current Clinical Urology, 2016)
This unique textbook is designed to provide a summary of state of the art developments in both male and female fertility and its association with cancer for both new and experienced practitioners. Clear, concise and readable, the text allows the reader to obtain rapid answers to this challenging medical issue. Special emphasis is placed on diagnostic and treatment algorithms. Topics covered include demographics of cancer in the reproductive age male, fertility conditions which predispose to cancer development, the role of assisted reproduction for fertility management, as well as fertility preservation strategies for the male and female cancer patients. Cancer and Fertility will be of great value to general urologists, uro-oncologists, gynecologists, medical oncologists, obstetricians, primary care providers, allied health providers.